Sex differences in prevalence rates and predictors of cigarette smoking among in-school adolescents in Kilimanjaro, Tanzania - Siziya, S; Ntata, P R; Rudatsikira, E; Makupe, C M; Umar, E; Muula, A S (Tanzania Journal of Health Research, 2008)
No Abstract. Tanzania Health Research Bulletin Vol. 9 (3) 2007: pp. 190-195